Herding Behavior of Business Groups During Covid-19: Evidence in Chile - Espinosa-Mendez, C (Universidad Nacional Autonoma de Mexico, 2023)
This article investigates whether herding behavior is present in stock returns of business groups during the COVID-19 pandemic. Using series of prices and daily traded volume of the companies that make up the General Index of Stock Prices of the Santiago de Chile Stock Exchange (S&P/CLIGPA) from January 1, 2010 to October 9, 2020 the results show herding behavior during COVID-19. Nevertheless, the herding behavior is weaker in business group firms compared to companies which are not affiliated to business groups. Then, when analyzing how herding behavior evolves in business groups during the presence of COVID-19, it is found that herding behavior changes to reverse herding behavior during May 2020 onwards. When inquiring about this point, it is found that herding behavior in business groups is lower under increasing uncertainty (number of cases and deaths due to COVID-19 increases). © 2023 Universidad Nacional Autónoma de México, Facultad de Economía.